If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+5x=9x
We move all terms to the left:
3x+5x-(9x)=0
We add all the numbers together, and all the variables
-x=0
x=0/-1
x=0
| 6-6x=6-6x | | 3x-5x=37 | | 8(x+3)+4=9(x+1) | | 5n+11-2n=-16 | | e+26=61 | | -3n+2n=8 | | 15+5x=5x+3*5 | | 2+(x-2)=10 | | 2x+2(1=2x)=3x-7 | | 0.005(4-k)+0.06(k-3)=1 | | 2(10+-1y)=2(-10)=20 | | -3a+8=14-8 | | 3+8x+11=0 | | 6(x-2)+x=3x+44 | | 26=1/2x-4 | | 7−x+3=9x10 | | 250+x=250 | | 16+7x=9x+2*5 | | -5x-17=-3x-15 | | 2(14+x)+x+x=836 | | 8+5x=5x+2*4 | | 20/8=y/12 | | 9x-(4x-6)=51 | | 2|4y+1|=4y+10 | | -3+16x=14x+13 | | 2/3z-8=11 | | 155÷66=m-(-2÷11) | | (18-6x)+(36+4x)=12-(4x-18) | | 21+5x=36 | | 10y=1000000000 | | 8/20=12/y | | 10x+50=15x |